PORTRAIT PROFESSIONAL SOCIAL WORKER MODERN TYPE - Хоменко-Семенова, Л. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The problem of determining the most important merit of specialist social work and its role in socialization, rights and responsibilities, the importance of professional activities